Response-to-Failure Analysis of Global Food System Initiatives: A Resilience Perspective - Agyemang, Prince; Kwofie, Ebenezer Miezah (Frontiers in Sustainable Food Systems, 2021)
International food system initiatives have led the efforts to combat the threats to global food security resulting from the failure of the current food systems. This study set out to investigate and assess the contributions of global food system initiatives in tackling the food system challenges. In assessing the food system initiatives, we develop a three-step methodology for Food System Initiative (FSI) selection and then conduct a qualitative evaluation using relevant indicators based on food system failure narratives. Furthermore, the authors synthesize present literature in the context of the extent to which coronavirus disease 2019 (COVID-19) pandemic has compounded food system challenges and, together with the response-to-failure analysis, recreate a resilient transformational framework, which will be an invaluable tool to FSI during and after the COVID-19 era, and guarantee we build back better. The findings show that while considerable effort is being made in addressing food system failures, the current COVID-19 pandemic has exacerbated the challenges and would require a paradigm shift not only in the implementation of conventional food system initiatives but also in the role of food system actors. The food system resilience framework presented provides useful pathway in expanding the understanding of the role of all key stakeholders and in identifying tipping points for building the desired resilience moving forward.